PENGARUH MANAJEMEN SUMBER DAYA MANUSIA TERHADAP MUTU LULUSAN DI SMPN SE-KECAMATAN AWANGPONE KABUPATEN BONE - Riswan, Muh.; Akbar, Sahrul; Patappa, Maghfira Maulani; Mangando, Widyaskara; Sari, Helena Purnama (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the influence of human resource management on the quality of graduates in junior high schools in Awangpone District, Bone Regency, South Sulawesi. The type of research used is ex post facto research by applying descriptive quantitative analysis to describe the real conditions in several junior high schools in Awangpone District, Bone Regency. The data collection technique was carried out by distributing questionnaires to respondents, namely educators. The sampling technique used was the Proportionate Stratafied Random Sampling technique which is part of Probability Sampling. The population in this sample was 76 people, therefore the sample of this study was 76 educators. The results of the study showed that Human Resource Management (X) has a significant influence on the quality of graduates (Y). The resulting equation is Y = 7.823 + 0.141 + 0.238, with a constant value of 7.823 and a coefficient for Human Resource Management (X) of 0.238. The results of the significance test show that the t-value for Human Resource Management (X) is 2.032 with a significance value of 0.046, which is smaller than the significance level (α) of 0.05. This indicates a significant influence between human resource management and graduate quality.